(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Rasa Shastra is a branch of Ayurveda which deals with the processing of minerals and metals having therapeutic importance. Rajata comes under the group of metals having high therapeutic values. Minerals and metals are mostly used in the form of bhasma. There is no specific anupana mentioned for Rajata, it depends upon dosha and disease. Rajata bhasma when given with proper Anupana is indicated in all types of diseases. Rajata Yoga is one such formulation mentioned in Rasa Tarangini, indicated in Prameha. Rajata bhasma, Twak churna, Ela churna and Patra churna are the main ingredients. The present study has been planned to standardize the method of preparation of a Herbo-mineral formulation i.e., Rajata Yoga. Samanya Shodhana and Visesha Shodhana procedures were adopted for Rajata patra (50g). After Visesha Shodhana, 48g of obtained coarse Rajata patra were subjected to Marana with equal quantity of Kajjali (48g) and sufficient quantity of Kumari Swarasa as bhavana dravya. Totally 25 putas were given to attain Rajata bhasma (90g) which passed all bhasma lakshanas as mentioned in our classics. Rajata bhasma (45g) was mixed with Trijataka churna (Twak churna-300g; Ela churna -300g and Patra churna – 300g) to form homogenous 945g of Rajata Yoga. Thus it can be concluded that Supaka i.e. neither less nor more heat is desirable and is essential for making a drug safe and efficacious.